How good can HDL Cholesterol be? Recent Evidence and way forward for Clinical Practice - Khan, Sikandar Hayat (Pakistan Armed Forces Medical Journal, 2023)
The science of “Lipidology” is flourishing in endless ways. The services included under the lipid testing do not provide generalised risk assessment for possible atherosclerotic cardiovascular disease (ASCVD) but provide specialised services, including genomic and molecular biomarkers for personalised care. The seminal discovery of lipoprotein fractions seems like a step next door in the much wider cosmos of metabolomics and proteomics, where knowledge of lipoprotein subfractions as villains or saviours seems like the trailer of the Larger Amphitheatre. Low-density lipoproteins (LDL) though differently defined in the literature, were categorised as “large buoyant LDL” (lbLDL) and “small dense LDL” (sdLDL).1 Over time, the knowledge base evolved to incorporate different fractions among lipoproteins based upon size and density with high-density lipoproteins (HDL) to incorporate nascent HDL, HDL2 and HDL3